Repensando o esporte na educação física escolar a partir de Cagigal - Derli Juliano Neuenfeldt; Marta De Salles Canfíeld (Universidade Federal do Rio Grande do Sul, 2001)
This article proposes characterize a sport for the school Physical Education based in the understanding of sport-practice ofCagigal.We settled down four fundamental principies: kinesthetic principie, because the sport is predominantly a physical activity; ludicrus principie, because the sport before everything is a game; agonistic principle, because there is no way to deny the competition and, the ethical principie, that offers values for the conduct ofwho practices sport. The sport-practice is an attempt o fsupplying to the professionals of Physical Education a sport vision that could contribute in the pupils' formation, teaching them to live in harmony with themselves and in society.